2020
DOI: 10.3389/fnagi.2020.594324
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Dysfunction and Its Association With Neuropathologic Proteins in Cerebrospinal Fluid From Patients With Parkinson Disease

Abstract: Background and Purpose: Olfactory dysfunction (OD) is a common non-motor symptom of Parkinson disease (PD). However, the relationship between OD and neuropathologic proteins in cerebrospinal fluid (CSF) from PD patients remains unclear.Methods: 166 PD patients were included in the study. Overall olfactory function was assessed by summing up the scores of olfactory threshold, discrimination, and identification by a Sniffin' Sticks test, based on which, patients were divided into PD with OD (PD-OD) and PD with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
3
3
0
Order By: Relevance
“…Pathological α-synuclein may cause damage to synapses and interrupt signal transmission, and ultimately lead to brain neuron death 32 . With PD progression, the macular inner retinal layer thickness is thinner, as confirmed in our findings above; astrocyte endocytosis is impaired; α-synuclein levels increase 33 ; and non-motor symptoms become more severe.…”
Section: Discussionsupporting
confidence: 83%
“…Pathological α-synuclein may cause damage to synapses and interrupt signal transmission, and ultimately lead to brain neuron death 32 . With PD progression, the macular inner retinal layer thickness is thinner, as confirmed in our findings above; astrocyte endocytosis is impaired; α-synuclein levels increase 33 ; and non-motor symptoms become more severe.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies indicate that olfactory function is impaired in α‐syn Tg mice 7,37–39 . In line with these findings, we found that α‐syn overexpressed mice developed dysosmia.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies indicate that olfactory function is impaired in αsyn Tg mice. 7,[37][38][39] In line with these findings, we found that α-syn overexpressed mice developed dysosmia. In addition to deficits in olfactory function, we observed a reduction in the mature olfactory neuron marker levels in the OB and OE of the α-syn Tg mice.…”
Section: Discussionsupporting
confidence: 83%
“…The cholinergic system is also dysfunctional in PD: atrophy of the nucleus basalis of Meynert, cognitive impairment and dementia. Cholinergic deficits are more pronounced in PD than in AD [76][77][78][79].…”
Section: Parkinson's Diseasementioning
confidence: 99%